2016
DOI: 10.1088/0022-3727/49/12/12lt01
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of spin waves and ferromagnetic resonance contribution to the spin pumping in a Ta/CoFeB structure

Abstract: The spin waves and ferromagnetic resonance (FMR) contribution to the spin pumping signal is studied in the Ta/CoFeB interface under different excitation bias fields. Ferromagnetic resonance is excited utilizing a coplanar waveguide and a microwave generator. Using a narrow waveguide of about 3 μm, magnetostatic surface spin waves with large wavevector (k) of about 0.81 μm -1 are excited. A large k value results in dissociation of spin waves and FMR frequencies according to the surface spin wave dispersion rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…It should be noted that in all samples Ta has been used as both seed and capping layers. Considering the high spin-orbit coupling in Ta, spin pumping effect may be another reason for the enhancement of α in these samples [31]. We observed that the value of α is increased in the Co/CFB bilayers (samples S3 and S4) as compared to the single layered Co and CFB thin films (i.e.…”
Section: Resultsmentioning
confidence: 74%
“…It should be noted that in all samples Ta has been used as both seed and capping layers. Considering the high spin-orbit coupling in Ta, spin pumping effect may be another reason for the enhancement of α in these samples [31]. We observed that the value of α is increased in the Co/CFB bilayers (samples S3 and S4) as compared to the single layered Co and CFB thin films (i.e.…”
Section: Resultsmentioning
confidence: 74%
“…spin current and charge was investigated by spin-torque ferromagnetic resonance (ST-FMR) [25][26][27][28][29][30][31][32][33].…”
mentioning
confidence: 99%